Rola edukacji sportowej w profilaktyce przemocy wśród młodzieży Ochotniczych Hufców Pracy = The role of sports education in preventing violence among young people in the Voluntary Labor Cors - Listwan, Teresa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents the problem of violence prevention among young people of the Voluntary Labor Corps as perceived by the educational staff of the Voluntary Labor Corps (OHP). The aim of the study was to answer the main research question, which was related to learning about the role played by sports education in the prevention of violence among the youth of the Voluntary Labor Corps. There were three specific research questions.
Keywords: sports education; physical culture; violence; Voluntary Labor Corps; youth; educational staff; edukacja sportowa; kultura fizyczna; przemoc; Ochotnicze Hufce Pracy; młodzież; kadra wychowawcza